Evaluation of a urinary metanephrines reagent kit: an automated approach - Thevarajah, M.T.; Nadarajah, S.; Chew, Y.Y.; Chan, P.C. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
The performance characteristics of automated sample preparation and auto-injection facilitate handling of larger number of samples as well as improve assay reliability.